Deictic Interpretation in TOEFL Reading: Strategies and Challenges of EFL Students - Sitti Aisyah; Muajiz Muallim; Cynic Tenedero; Munawir (Foreign Language Instruction Probe, 2026)
This study aims to explore the understanding of English language education students of the phenomenon of Deixis in the TOEFL reading text and identify the factors that influence the understanding. As a crucial pragmatic competence in academic literacy, Deixis acts as a bridge that connects text with context. This study uses a descriptive qualitative approach by involving students of the English Language Education Program, IAIN Parepare, as informants. Data were collected through the TOEFL reading test and stimulated recall interview to reveal students ' cognitive processes. The results showed that students ' understanding was at a mechanistic-literal level. Students demonstrate a good understanding of the Deixis persona because of its concrete and explicit nature of reference. However, a significant decrease in understanding occurs in temporal Deixis and Discourse Deixis; students tend to experience chronological confusion and difficulty tracking abstract references that cross paragraph boundaries. The proximity approach strategy, which is the tendency to choose references based on physical proximity in the text, is the dominant method used by students when dealing with ambiguity. These findings indicate that the main barriers for STEM students are limited vocabulary, short-term memory load (cognitive overload), and dependence on surface reading strategies (surface reading).